FEATURES OF USE OF METALANGUAGE MEANS IN MODERN ENGLISH NEWSPAPERS - J. Pirverdieva (Гуманитарные и юридические исследования)
The article is devoted to the sociolinguistic features of the British press, correlating with their information-content and impact potential on the reader through various metalanguage means. The study of newspaper discourse and the revealing of metalanguage in it by means of metalanguage operators testify to the ability to determine, irstly, lexis from the point of view of origin, secondly, the set of sublanguages of the modern speaker and, thirdly, dynamic processes in lexis. Newspaper discourse as a process of verbal communication in print media is manifested by a dynamic cognitive-communicative phenomenon. The text of the newspaper is characterized by the fact that it quickly reflects and ixes numerous changes in linguistic reality. The informational content function with the persuasion function combined in such a text is expressed by various metalinguistic means. The metalanguage of the newspaper is "built" by means of meta-operators, which may indicate, irstly, a set of sublanguages of the modern speaker, secondly, vocabulary from the point of view of origin and, thirdly, dynamic processes in vocabulary. Thus, the paper presents the results of the analysis of metalinguistic means in modern English newspapers, iden-tiies various language techniques as one of the main reasons for the intensiication of linguistic relection of modern publicism. A native speaker often comments on words in terms of their origin. Socio-economic and cultural ties between linguistic groups, as well as the development of ethnic contacts contribute to the process of borrowing foreign language vocabulary. The speaker often enriches his speech with foreign words that are labeled with meta-operators. Pointing to borrowing, the speaker also expresses, through the meta-operators, an evaluative attitude toward the foreign word. Meta-operators pointing to dynamic processes in the vocabulary show that the vocabulary of the language develops according to the processes occurring in it: constant replenishment with new words and the disappearance of obsolete words. Due to the fact that the sociolinguistic features of the modern press, in general, and the English, in particular, are interdependent with the dynamics of metalinguistic means, the work also classiies metalinguistic means of a newspa- per language according to graphic and orthographic signs punctuation marks and font.